Iron Deficiency in Female Endurance Athletes: The Role of Hepcidin Regulation, Training Load, and Dietary Strategies in Optimizing Performance and Health - Małgorzata Wasilewska; Krzysztof Pietrzak; Sebastian Polok; Łukasz Bialic (Quality in Sport)
Purpose: Examine iron deficiency (ID) mechanisms in female endurance athletes, focusing on hepcidin dysregulation, training impacts, and dietary strategies.